Maximizing performance of fuel cell using artificial neural network approach for smart grid applications - Bicer, Y.; Dincer, I.; Aydin, M. (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
This paper presents an artificial neural network (ANN) approach of a smart grid integrated proton exchange membrane (PEM) fuel cell and proposes a neural network model of a 6 kW PEM fuel cell. The data required to train the neural network model are generated by a model of 6 kW PEM fuel cell. After the model is trained and validated, it is used to analyze the dynamic behavior of the PEM fuel cell. The study results demonstrate that the model based on neural network approach is appropriate for predicting the outlet parameters. Various types of training methods, sample numbers and sample distribution methods are utilized to compare the results. The fuel cell stack efficiency considerably varies between 20% and 60%, according to input variables and models. The rapid changes in the input variables can be recovered within a short time period, such as 10 s. The obtained response graphs point out the load tracking features of ANN model and the projected changes in the input variables are controlled quickly in the study. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: PEM fuel cells; Hydrogen; Smart grid; Artificial neural network; Energy; Efficiency; ENERGY MANAGEMENT; MODEL; OPTIMIZATION; SYSTEM; Thermodynamics; Energy & Fuels